Application of Augmented Reality for Furniture Catalogs - Hamzah Fachrurozi; Adityo Permana Wibowo (Journal of Social Research, 2023)
In the current rapidly developing era of technology and telecommunications, promotional media has become a crucial factor in business, particularly for furniture stores. Although the use of sales catalogs in print media is already common, it often leaves customers dissatisfied because it is only two-dimensional and requires a visit to the store. Therefore, more attractive and innovative promotional media is necessary to increase the appeal and sales value of a store. One technology that can be utilized for this purpose is Augmented Reality (AR) technology, which combines the real and virtual worlds in an Android-based catalog. A catalog application with AR technology can display furniture products in real-time and facilitate customers in selecting furniture by presenting a 3D image of the product from various angles. It is expected that customers will be more interested in furniture catalogs that use Augmented Reality technology and increase the store's sales value.